The Innovation and its Effect on Temporary and Permanent Hiring in the Manufacturing Sector - Vélez Osorio, Iris María (2021)
This analysis seeks to understand investment in innovation and innovation in organizational methods as two fundamental factors for superior job creation in the manufacturing sector, in 56 subsectors containing 8,264 companies, based on a model of structural equations. Some previous studies are contradictory, so this study allows us to recognize that investment in innovation allows greater generation of permanent employment, while innovation in organizational methods improves the generation of temporary employment. For manufacturing organizations and the sector, it is of great importance to recognize the effects of innovation on job creation, since job creation is essential to improve the economic cycle, especially with the current drop in employment that the sector and context are experiencing. Keywords: innovation, employment, long-term employees, temporary employees.